A Compact Overview on Li-Ion Batteries Characteristics and Battery Management Systems Integration for Automotive Applications - Andrea Ria; Pierpaolo Dini (Energies)
The transition to sustainable mobility is progressing rapidly, with electric vehicles (EVs) playing a pivotal role in lowering greenhouse gas emissions and reducing the reliance on fossil fuels. At the core of this transformation are lithium-ion batteries (Li-ion), valued for their high energy density and long cycle life. However, the increasing demand for EVs necessitates continuous improvements in battery technology and the integration of advanced systems to ensure safe, efficient, and reliable performance. This review offers a clear and comprehensive summary of the latest innovations in Li-ion battery chemistry, battery pack design, and Battery Management System (BMS) functionalities. Unlike other reviews, this work emphasizes practical considerations, such as voltage, power, size, and weight for commercial vehicles. It also addresses integrated safety solutions, including disconnection systems and pre-charge circuits, which are vital for enhancing battery safety and lifespan. Additionally, it explores key BMS functions, like cell monitoring, balancing, and thermal management, all crucial for maximizing battery performance and ensuring safe operation. By consolidating current research and industry practices, this article provides essential information in a concise yet accessible format. It enables researchers to quickly gain a solid understanding of the field, distinguishing itself from reviews that focus on narrower aspects of battery technology. Its holistic approach delivers valuable insights for improving EV charging systems’ safety and performance, making it a highly useful resource for researchers and industry professionals alike.